Neuroprotective and Neurotoxic Effects of Glial-Derived Exosomes - Oyarce, Karina; Cepeda, María Yamila; Lagos, Raúl; Garrido, Camila; Vega-Letter, Ana María; Garcia-Robles, María; Luz-Crawford, Patricia; Elizondo-Vega, Roberto (Frontiers in Cellular Neuroscience, 2022)
Exosomes derived from glial cells like astrocytes, microglia and oligodendrocytes can modulate cell communication in the brain and exert protective or neurotoxic effects on neurons, depending on the environmental context upon its release. Their isolation, characterization, and analysis under different conditions in vitro and in animal models has allowed them to expand the molecular mechanisms behind neuroinflammation and neurodegeneration spreading, and to propose its use as potential diagnostic tools. Moreover, the discovery of specific molecular cargos, such as cytokines, membrane-bound and soluble proteins (neurotrophic factors, growth factors, misfolded proteins), miRNA and long-non-coding RNA, that are enriched in glial-derived exosomes with neuroprotective or damaging effects, or their inhibitors can now be tested as therapeutic tools. In this review we summarize the state of the art on how exosomes secretion by glia can affect neurons and other glia from the central nervous system in the context of neurodegeneration and neuroinflammation, but also, on how specific stress stimuli and pathological conditions can change the levels of exosome secretion and their properties.